PERAN UNIT PEMBANTU PELAYANAN MUSIK GEREJA DALAM MEMBANGUN IBADAH JEMAAT GMIT ANUGERAH ATAMBUA - Yefta Bako; Patce Orianus Snae; Cici Nullik; Frengki Metkono (Institut Agama Kristen Negeri Kupang, 2022)
Church Musik Service Assistant Unit (UPP) is a collection of assemblies that have been confirmed/legitimated to manage music services in every worship service. The purpose of this study was to find out how the church music UPP played it’s role in building sunday worship at the GMIT Anugerah Atambua Congregation by using qualitative methods and observing participation an informational role, decision maker and resource allocator to build sunday worship with 4 stages of management functions consisting of planning, coordinating, directing and supervising stages.